Technical efficiency of organic caisim farming using Data Envelopment Analysis (DEA) - Apolinaris, Florida; Sa'diyah, Ana Arifatus; Wulandari, Ayu; Suliana, Gatot; Lakmali, Appuwa Wedalage Sudarshani (Journal of Agricultural Socio-Economics (JASE), 2024)
This study aims to assess the level of technical efficiency in organic caisim (mustard green) farming and identify the socio-economic factors influencing it among farmers in the Organic Farming Group of Sumberejo Village, Batu City. Technical efficiency is a crucial indicator for optimizing input use in agricultural production, yet it remains underexplored in the context of organic vegetable farming. The research employs the Data Envelopment Analysis (DEA) method using the Variable Return to Scale (VRS) input-oriented model to evaluate technical efficiency, while Tobit regression is utilized to examine the determinants of efficiency levels. Results indicate that the average technical efficiency score among respondent farmers is 0.737, suggesting suboptimal input utilization and room for improvement in production practices. The Tobit regression results indicate that age has a negative and significant impact on technical efficiency. This suggests that older farmers are less likely to adopt innovative or adaptive farming practices, which can limit their ability to optimize input use. In contrast, farming experience shows a positive and significant effect, reflecting the value of accumulated practical knowledge and improved decision-making in managing resources efficiently. Meanwhile, education level and household size do not exhibit a significant influence on technical efficiency. This finding implies that, in the context of small-scale organic farming, formal education may not be as critical as experiential learning, and a larger household does not necessarily enhance labor productivity without effective role distribution and management. The study is limited to a localized farming group and a specific organic crop, warranting broader investigations for general applicability. Nevertheless, it offers valuable insights into technical efficiency in sustainable farming practices.